SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN BUAH NAGA MENGGUNAKAN TEOREMA BAYES - Muhammad Misbahul Munir (Informasi Interaktif, 2020)
Dragon fruit is a plant that has a lot of benefits and special appeal in society. Currently dragon fruit plantations in Indonesia are growing very rapidly. Dragon fruit grows and is cultivated in almost all parts of the archipelago, whether it is individual property or company property. This plant contains many properties that make dragon fruit demand high.Expert system itself is artificial intelligence that uses specific knowledge to map problems at the expert level. One application of the expert system is in the field of plantations to diagnose diseases in plants. In this study, the design and manufacture of an expert system used to help diagnose a disease in dragon fruit and determine suggestions or treatment solutions for dragon fruit.The result of this paper is an expert system to diagnose dragon fruit plant diseases along with the probability value of the diagnosed disease which shows the level of system confidence in the disease and suggestions or treatment solutions for the dragon fruit. Keywords : Expert system, Dragon Fruit, diagnostics